A framework for video transcoding and management in cloud manufacturing. (2016) - Zhou, Jian; Zuo, Ying
Cloud-based manufacturing has been defined as CMfg. It is a system built on cloud computing technology that can integrate a large number of manufacturing resources. In a CMfg system, there are huge amounts of data and one of them is the video used to monitor manufacturing processes and learn knowledge. In cloud platform, the video data generate fast and have diverse formats, so the need for unified transcoding and management is necessary. In this article, an elastic cloud framework for fast video transcoding process and management is proposed. The core of this framework is a distributed system based on Hadoop that is designed for massive data storage and parallel computing.